2021
DOI: 10.1158/1535-7163.mct-21-0037
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Attenuation Inhibits Tumor Growth and Promotes Differentiation in a BRAFV600E-Driven Thyroid Cancer Animal Model

Abstract: BRAFV600E mutation is the most frequent genetic alteration in papillary thyroid cancer (PTC). β-Catenin (Ctnnb1) is a key downstream component of canonical Wnt signaling pathway and is frequently overexpressed in PTC. BRAFV600E-driven tumors have been speculated to rely on Wnt/β-catenin signaling to sustain its growth, although many details remain to be elucidated. In this study, we investigated the role of β-catenin in BrafV600E-driven thyroid cancer in a transgenic mouse model. In BrafV600E mice with wild-ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Clinical investigation has shown that the cumulative RAI received by patients significantly and positively correlates with β‐catenin expression 44 . In BRAF V600E ‐induced PTC mouse model, Ctnnb1 deletion resulted in up‐regulated Nis so as to increased iodine uptake 3 . Since miR‐31 is indispensable for BRAF V600E ‐induced PTC due to its regulation on Wnt/β‐catenin pathway, we asked whether miR‐31 is involved in PTC dedifferentiation and RAI refractoriness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical investigation has shown that the cumulative RAI received by patients significantly and positively correlates with β‐catenin expression 44 . In BRAF V600E ‐induced PTC mouse model, Ctnnb1 deletion resulted in up‐regulated Nis so as to increased iodine uptake 3 . Since miR‐31 is indispensable for BRAF V600E ‐induced PTC due to its regulation on Wnt/β‐catenin pathway, we asked whether miR‐31 is involved in PTC dedifferentiation and RAI refractoriness.…”
Section: Resultsmentioning
confidence: 99%
“… 44 In BRAF V600E ‐induced PTC mouse model, Ctnnb1 deletion resulted in up‐regulated Nis so as to increased iodine uptake. 3 Since miR‐31 is indispensable for BRAF V600E ‐induced PTC due to its regulation on Wnt/β‐catenin pathway, we asked whether miR‐31 is involved in PTC dedifferentiation and RAI refractoriness. Indeed, GSEA analysis showed that low miR‐31 enriched for genes involved in thyroid hormone metabolic processes (Figure S7A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[14][15][16] Previous studies have also shown that inducing dedifferentiation or restoring Wnt signaling stimulates BRAF V600E -driven tumorigenesis. 11,13,18,23,68,69 Elevated Wnt signaling is also common to both the genetic mouse models of BRAF V600E -driven SCRC. 11 Consistent with that precursor intestinal lesions with BRAF V600E mutation progress to cytologic dysplasia only after they acquire Wnt pathway activity.…”
Section: Discussionmentioning
confidence: 99%